2020
DOI: 10.3390/coatings10100993
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Characterization of Ceramic Coating on Al7075 Alloy by Plasma Electrolytic Oxidation in Molten Salt

Abstract: The fabrication of a ceramic coating on the metallic substrate is usually applied to achieve the improved performance of the material. Plasma electrolytic oxidation (PEO) is one of the most promising methods to reach this performance, mostly wear and corrosion resistance. Traditional PEO is carried out in an aqueous electrolyte. However, the current work showed the fabrication and characterization of a ceramic coating using PEO in molten salt which was used to avoid disadvantages in system heating-up and the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 31 publications
1
10
0
1
Order By: Relevance
“…A-type discharges occur on the surface of PEO coatings. Type B refers to strong discharges between PEO coatings and the substrate surface, and during this process, a number of molten oxides eject instantaneously from the discharge channels, which forms a relatively large-size "pancake" structure on the surface of the coatings [23][24][25]. C-type discharges occur under PEO coatings.…”
Section: Morphology and Phase Composition Of Peo Coatingsmentioning
confidence: 99%
“…A-type discharges occur on the surface of PEO coatings. Type B refers to strong discharges between PEO coatings and the substrate surface, and during this process, a number of molten oxides eject instantaneously from the discharge channels, which forms a relatively large-size "pancake" structure on the surface of the coatings [23][24][25]. C-type discharges occur under PEO coatings.…”
Section: Morphology and Phase Composition Of Peo Coatingsmentioning
confidence: 99%
“…It was found that the addition of graphite reduced the surface porosity of oxide film, improved the mechanical and tribological properties of oxide film, and extended the service life of the composite oxide film [1]. Sobolev uses Plasma electrolytic oxidation to perform surface treatment on 7075 aluminum alloy and found that the addition of oxide coating has significantly improved the corrosion resistance [6]. The surface modification treatment technology used in the above industrial production does not affect the aluminum alloy matrix and also gives the aluminum alloy surface better performance and improves its range of applications.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of PEO coated Al alloys 4 works are dedicated to cover different features [8][9][10][11]. The research published by del Olmo et al [8] investigates environmentally friendly alternatives to toxic Cr (VI)-based surface treatments for corrosion protection of Al alloys focused on multifunctional PEO-layered double hydroxides (LDH) coatings.…”
mentioning
confidence: 99%
“…Moving to other properties, the production of phosphorescent coatings is reported by Auzins [10] using Sr0.95Eu0.02Dy0.03Al2O4-δ powder and Plasma Electrolytic Oxidation. In addition, Sobolev et al [11] investigates the use of molten salt during the development of PEO coatings on AA7075 from the point of view of fabrication and characterization.…”
mentioning
confidence: 99%